Mosquito bites and stage-specific antibody responses against Plasmodium falciparum in southern Ghana - Kwapong, S.S.; Asare, K.K.; Kusi, K.A.; Amoah, L.E.; et al. (Malaria Journal, 2023)
Background The human host elicits specific immune responses after exposure to various life stages of the malaria parasite as well as components of mosquito saliva injected into the host during a mosquito bite. This study describes differences in IgG responses against antigens derived from the sporozoite (PfCSP), asexual stage parasite (PfEBA175) and the gametocyte (Pfs230), in addition to an Anopheles gambiae salivary gland antigen (gSG6-P1), in two communities in Ghana with similar blood stage malaria parasite prevalence. Methods This study used archived plasma samples collected from an earlier cross-sectional study that enrolled volunteers aged from 6 months to 70 years from Simiw, peri-urban community (N=347) and Obom, rural community (N=291). An archived thick and thin blood smear for microscopy was used for the estimation of Plasmodium parasite density and species and DNA extraction from blood spots and P. falciparum confirmation was performed using PCR. This study used the stored plasma samples to determine IgG antibody levels to P. falciparum and Anopheles salivary antigens using indirect ELISA. Results Individuals from Simiw had signifcantly higher levels of IgG against mosquito gSG6-P1 [median (95%CI)] [2.590 (2.452–2.783) ng/mL] compared to those from Obom [2.119 (1.957–2.345) ng/mL], p<0.0001. Both IgG responses against Pfs230proC (p=0.0006), and PfCSP (p=0.002) were signifcantly lower in volunteers from Simiw compared to the participants from Obom. The seroprevalence of PfEBA-175.5R (p=0.8613), gSG6-P1 (p=0.0704), PfCSP (p=0.7798) IgG were all similar in Obom and Simiw. However, Pfs230 seroprevalence was significantly higher at Obom compared to Simiw (p=0.0006). Spearman correlation analysis showed no significant association between IgG responses against gSG6-P1, PfCSP, Pfs230proC and PfEBA-175.5R and parasite density at both Obom and Simiw (p>0.05). Conclusion In conclusion, the study showed that participants from Simiw had higher concentrations of circulating gSG6-P1 IgG antibodies but lower concentrations of P. falciparum antibodies, PfCSP IgG and Pfs230proC IgG compared to participants from Obom.
Research Article
Keywords: Plasmodium falciparum; Circumsporozoite surface protein (PfCSP)